Honoring the wild : reclaiming witchcraft and environmental activism - Moon, Irisanya (Earth spirit, 2023)
Deeply rooted in environmentalism and activism, Honoring the Wild answers crucially pertinent questions while driving at lasting change. From political demonstrations to personal calls, Irisanya Moon offers a collection of stories and lessons, as told by Reclaiming Witches from around the world, about the facts and fears, the confessions and collaborations within the Reclaiming tradition's own timeline of activism. Honoring the Wild inspires and informs creativity and purpose while reminding us of all that has come and of all that is left to do. May the wild be blessed and healed by this spell of intention and inspiration. -- Back cover.